PENGARUH PENDAPATAN TRANSFER DAN SILPA TERHADAP BELANJA MODAL DI KABUPATEN MAMBERAMO TENGAH - Efendi Jikwa; Agustinus Salle; Paulus K. Allo Layuk (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2017)
This study attempts to know whether income transfers and remaining budget (SILPA) have positive impact on capital expenditure in Mamberamo Tengah Regency. Methods used in this research to cultivate and analyzed data and information using a qualitative approach (descriptive) and quantitative. Technique of analysis in this research consisting of descriptive analysis and statistical analysis. The value of influence done by estimating the coefficients using the concept of ordinary least square (OLS). The results show that: (a) based on the qualitative approach through a method of linear seen that the transfer of the central government through a source of share funds (DBH), general allocation funds (DAU), special allocation funds (DAK) and special autonomy (Otsus) have the proportion of capital spending influence, this can be seen from the coefficients above all having a positive sign. Sources of share funds (DBH) has an influence that was dominant compared with other sources of funds, (b) through the estimation results of the regression coefficient obtained that SILPA affects capital spending in a positive way, this is supported with a value of a coefficient at 83,9 percent (marked positive). Keyword: APBD, DBH, DAU, DAK, OTSUS, SiLPA, capital expenditure, balancing funds